Nature-Based Metaphors in Selected Niki’s Song Lyrics: A Semantic Study of Emotional Expression - Asna Pratiwi; Christianti Tri Hapsari Hapsari (Universitas Islam Negeri Palopo, 2026)
This article examines the use of nature-based metaphors in the lyrics of five NIKI songs – “Anaheim,” “Backburner,” “Oceans & Engines,” “Autumn,” and “La La Lost You.” This study aims to identify, classify, and interpret the emotional functions of nature-based metaphors, specifically ocean, fire, storms, and seasonal cycles, to articulate various emotional states, including grief, unrequited love, and the search for autonomy. Based on Lakoff and Johnson's Conceptual Metaphor Theory, this study views metaphors not merely as stylistic ornaments but as cognitive mechanisms that help listeners understand abstract emotional states through concrete natural phenomena. Using qualitative descriptive methods, the analysis reveals that NIKI's use of connotative language transforms subjective experiences into universal emotional narratives. The results identified a total of 101 nature-based metaphorical expressions across the selected songs. The findings reveal three main types of metaphors: ontological metaphors (46.5%), structural metaphors (38.6%), and orientational metaphors (14.8%). Ontological metaphors are the most common, demonstrating a lyrical strategy for materializing abstract internal pain into tangible substance. Semantically, NIKI utilizes the domain of nature. These metaphors enrich emotional expression: for example, the fire metaphor deepens the nuances of emotional intensity, while the water and sky metaphors communicate longing, sadness, or relief. A comparison between the songs reveals how each metaphor highlights different emotional patterns, yet they are conceptually related.